2020
DOI: 10.1007/978-3-030-52246-9_34
|View full text |Cite
|
Sign up to set email alerts
|

An Internet of Things and Blockchain Based Smart Campus Architecture

Abstract: Rapid development in science and information technologies, such as the Internet of things, has led to a growth in the number of studies and research papers on smart cities in recent years and more specifically on the construction of smart campus technologies. This paper will review the concept of a smart campus, discuss the main technologies deployed, and then propose a new novel framework for a smart campus. The architecture of this new smart campus approach will be discussed with particular consideration of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…The Society 5.0 framework envisages the Smart Campus as a digitally advanced and interconnected system that uses cutting-edge technology to elevate the quality of education, research, and campus life [33]. As the Smart Campus operates through interconnected devices and data exchange, it is crucial to ensure the security and privacy of personal information and campus assets through cybersecurity and blockchain [34]. By implementing measures such as access controls, identity management, and threat detection systems, cybersecurity can prevent malicious attacks and data breaches in the Smart Campus.…”
Section: Cybersecurity and Blockchain In Smart Gridsmentioning
confidence: 99%
“…The Society 5.0 framework envisages the Smart Campus as a digitally advanced and interconnected system that uses cutting-edge technology to elevate the quality of education, research, and campus life [33]. As the Smart Campus operates through interconnected devices and data exchange, it is crucial to ensure the security and privacy of personal information and campus assets through cybersecurity and blockchain [34]. By implementing measures such as access controls, identity management, and threat detection systems, cybersecurity can prevent malicious attacks and data breaches in the Smart Campus.…”
Section: Cybersecurity and Blockchain In Smart Gridsmentioning
confidence: 99%
“…The smart campus network grid is the bedrock of creating a smart campus. Learning institutions need to develop smart buildings on campus [5,57,88,90,93,94]. Betancur et al [95] suggested social participation in smart cities development.…”
Section: Smart Campus Network Gridmentioning
confidence: 99%
“…Table 12 focused more on higher education, teaching and learning applications of IT. Mobile applications are useful for timetabling, attendance monitoring, communication, and feed back purposes [2,90,115]. More importantly, mobile applications have become useful in teaching and learning using Microsoft applications.…”
Section: Smart Campus Applicationsmentioning
confidence: 99%
See 2 more Smart Citations